Предмет: Алгебра,
автор: Stafeeva75
(х+6)^2=(х+9)^2
(7-х)^2=(х+3)^2
Решите уравнения, пожалуйста
Ответы
Автор ответа:
0
(х+6)²=(х+9)²,
х²+12х+36=х²+18х+81,
12х+36=18х+81,
12х-18х=81-36,
-6х=45,
х=-7,5.
Ответ: -7,5.
(7-х)²=(х+3)²,
49-14х+х²=х²+6х+9,
49-14х=6х+9,
-14х-6х=9-49,
-20х=-40,
х=2.
Ответ: 2.
х²+12х+36=х²+18х+81,
12х+36=18х+81,
12х-18х=81-36,
-6х=45,
х=-7,5.
Ответ: -7,5.
(7-х)²=(х+3)²,
49-14х+х²=х²+6х+9,
49-14х=6х+9,
-14х-6х=9-49,
-20х=-40,
х=2.
Ответ: 2.
Автор ответа:
0
задачи выполнена ответ в вложений
Приложения:
Автор ответа:
0
Спасибо
Похожие вопросы
Предмет: Математика,
автор: samsunga30s18702
Предмет: Английский язык,
автор: Ciganator
Предмет: Другие предметы,
автор: afrinxhsjsk18
Предмет: Математика,
автор: ebirykov
Предмет: Алгебра,
автор: Вовчиксмайл